Taxonomy and phylogeny of Fusarium houttuyniae and F. liriopes spp. nov. (Hypocreales, Nectriaceae) from China - He, Yu-Ke; Jayawardena, Ruvishika S.; Kakumyan, Pattana; Wang, Yong (Phytotaxa, 2023)
Moniliaceous hyphomycetes were collected from leaves of Houttuynia cordata and Liriope platyphylla in Guang Xi Medicinal Botanical Garden, Guangxi Province, China. Morphological characteristics and multi-gene phylogenetic analyses of the calmodulin (cmdA), RNA polymerase II second largest subunit (rpb2), translation elongation factor 1-alpha (tef1), and β-tubulin (tub2), showed that four Fusarium strains represent two novel species viz. Fusarium houttuyniae and F. liriopes spp. nov and are introduced with full descriptions, illustrations, and notes herein.